A Low-Profile Metasurface MIMO Antenna with Suppressed Higher-Order Modes for 5G Applications - Hamed Hamlbar Gerami; Robab Kazemi (AUT Journal of Electrical Engineering)
In this paper, a novel low-profile and low cross-polarization metasurface antenna is proposed for 5G mm-wave applications. The proposed antenna consists of two layers, with a slot antenna as the base and a novel metasurface layer on top. The metasurface layer is a 3×3 array of patches. By strategically incorporating slits and stubs within the middle patches, the undesired degenerate mode is separated from the fundamental mode, and higher-order modes are suppressed that typically appear in conventional metasurfaces. Additionally, rectangular slots are added in the middle of the corner patches to shift higher-order modes to frequencies beyond the desired operating bandwidth, mitigating issues such as beam splitting and beam squint in the radiation patterns. Experimental measurements demonstrate that the proposed metasurface antenna operates over a bandwidth of 25.14% (23.3 GHz to 30 GHz), with a return loss better than 10 dB, a peak gain of 8.1 dB, and an XP level lower than -26 dB and -53 dB at  and  planes, respectively. Compared to conventional metasurface antennas, our design reduces the antenna dimension by 62%, resulting in a compact size of 0.72λ0 × 0.72λ0 × 0.08λ0. Furthermore, we validate the performance of the single-element antenna by employing it in a 2×2 Multiple Input-Multiple Output (MIMO) configuration without requiring additional inter-element spacing. The MIMO antenna exhibits promising performance as well. Overall, our proposed low-profile and low cross-polarization metasurface antenna shows great potential for 5G mm-wave applications, offering improved efficiency and reduced size compared to conventional designs.